Pengaruh Berbagai Konsentrasi Larutan Propolis dalam Menghambat Pertumbuhan Bakteri Aggregatibacter Actinomycetemcomitans (AA) Penyebab Periodontitis - Pratama, Rizqia Lintang; , drg. Ana Riolina, MPH; , drg. Nanang Krisnawan (2015)
Periodontal disease was common disease found on people nowdays, one of them was known as periodontitis. Periodontitis caused by gram negative anaerobic bacteria called Aggregatibacter actinomycetemcomitans (Aa). Propolis was a bee product that contain active compound which could inhibit bacteria growth. The study was conducted to understand the effect of various propolis solution againts Aa growth. This was purely experimental laboratory study with post test only group design. Antimicrobial susceptibility was tested using disk diffusion method. The sample were divided into five treatment groups and twi control groups. Material test consistend of propolis solution, povidone iodine as positive control and aquades as negative control. Propolis solution were prepared into 5 differetny concentration, 30%, 40%, 50%, 60%, 70%, positive control, negative control and were replicated 3 times than incubated 24 hours within 37°C. Clear zone that appeared around the disk were measured by millimeter caliper. The result showed that propolis solution with 30%, 40%, 50%, 60%, 70% concentration could give effective antimicrobial susceptibility against Aa growth (p=0.000). It can be concluded that various propolis solution could affect Aa growth, while the most effective solution to inhibit was 70% concentration